Impact of KRAS mutation on response and outcome of patients with stage III non‐squamous non‐small cell lung cancer. Issue 10 (18th August 2015) - Yagishita, Shigehiro; Horinouchi, Hidehito; Sunami, Kuniko S.; Kanda, Shintaro; Fujiwara, Yutaka; Nokihara, Hiroshi; Yamamoto, Noboru; Sumi, Minako; Shiraishi, Kouya; Kohno, Takashi; Furuta, Koh; Tsuta, Koji; et al.
Abstract : The frequency and clinical profile of patients with stage III non‐small cell lung cancer harboring KRAS mutations have not yet been well documented. Here, we analyzed hotspot KRAS mutations using high‐resolution melting analyses in tumor specimens from patients who received chemoradiotherapy between January 2001 and December 2010 at the National Cancer Center Hospital. The associations between the presence of KRAS mutations and the response rate, relapse‐free survival, first relapse sites, survival post‐progression and overall survival were investigated. A total of 274 non‐squamous non‐small cell lung cancer patients received chemoradiotherapy at our hospital. After excluding 121 patients for whom tumor specimens were not available and 34 patients with EGFR mutations, the remaining 119 patients were included in the analysis. KRAS mutations were found at a frequency of 13%. Patients with KRAS mutations had a shorter median relapse‐free survival (6.1 vs 10.9 months) and a lower response rate (63% vs 81%). As for the first relapse site, patients with KRAS mutations had fewer local relapses (8% vs 23%) and more brain metastases (46% vs 12%). After disease progression, patients with KRAS mutations had a significantly shorter median survival post‐progression (2.5 vs 7.3 months, P = 0.028) and median overall survival (15.1 vs 29.1 months, P = 0.022). Our results suggested that KRAS mutation could be associated with a reduced efficacy of chemoradiotherapy and a shortened survival time. Abstract : Here we conducted KRAS mutation analysis for the aim of understanding the significance of KRAS mutations in patients with stage III non‐squamous non‐small cell lug cancer treated with chemoradiotherapy. Patients with KRAS mutation had a shorter median relapse‐free survival, a lower responce rate, significantly shorter median survival post‐progression, and median overall survival. Our results suggested that KRAS mutation is associated with a reduced efficacy of CRT and a shortened survival time.